1998
DOI: 10.1128/mcb.18.12.7499
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Pancreatic Eukaryotic Initiation Factor 2 α-Subunit Kinase, PEK, Involved in Translational Control

Abstract: In response to various environmental stresses, eukaryotic cells down-regulate protein synthesis by phosphorylation of the ␣ subunit of eukaryotic translation initiation factor 2 (eIF-2␣). In mammals, the phosphorylation was shown to be carried out by eIF-2␣ kinases PKR and HRI. We report the identification and characterization of a cDNA from rat pancreatic islet cells that encodes a new related kinase, which we term pancreatic eIF-2␣ kinase, or PEK. In addition to a catalytic domain with sequence and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
563
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 743 publications
(596 citation statements)
references
References 51 publications
16
563
0
7
Order By: Relevance
“…Instead, its half life increased 2-fold indicating a decrease in ERAD. Therefore, rapid decrease of αTCR levels upon treatment with SubAB must be explained by another mechanisms such as global inhibition of protein synthesis (Harding et al, 1999;Shi et al, 1998), which we have indeed confirmed directly. In untreated cells, αTCR probably accounts for a significant fraction of total ERAD, while under ER stress induced by BiP depletion, remaining αTCR must compete for the ERAD machinery with a plethora of endogenous misfolded proteins.…”
Section: Discusssionsupporting
confidence: 76%
See 1 more Smart Citation
“…Instead, its half life increased 2-fold indicating a decrease in ERAD. Therefore, rapid decrease of αTCR levels upon treatment with SubAB must be explained by another mechanisms such as global inhibition of protein synthesis (Harding et al, 1999;Shi et al, 1998), which we have indeed confirmed directly. In untreated cells, αTCR probably accounts for a significant fraction of total ERAD, while under ER stress induced by BiP depletion, remaining αTCR must compete for the ERAD machinery with a plethora of endogenous misfolded proteins.…”
Section: Discusssionsupporting
confidence: 76%
“…During ER stress, BiP preferentially binds to misfolded proteins within the ER, therefore BiP detaches from the lumenal domains of those proteins, which now interact, oligomerize and trigger signaling events leading to UPR. Active PERK phosphorylates eIF2α, leading to a generalized repression of translation (Harding et al, 1999;Shi et al, 1998) associated with a selective translation of mRNAs bearing upstream open reading frames such as ATF3 and ATF4 (Shen et al, 2004). Active IRE1 mediates a unique cytosolic splicing of the mRNA coding for the XBP1 transcription factor (Yoshida et al, 2001) as well as generalized degradation of ER-associated mRNAs (Hollien and Weissman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It contains a luminal regulatory domain and cytoplasmic elF2a kinase domain that is conserved among the four-member family of kinase that regulate translation initiation in mammals [5,22]. PERK is negatively regulated by the ER chaperones 78 kDa glucose-regulated protein/Immunoglobulin heavy chain-binding protein (GRP78/BIP) and 94 kDa glucoseregulated protein (GRP94).…”
Section: Introductionmentioning
confidence: 99%
“…The proximal effectors of the mammalian UPR include the three homologous, ER-resident transmembrane protein kinases Ire1 (␣ and ␤) and PKR-like ER kinase (PERK); the ER-resident transmembrane protease caspase 12; and the ER-resident transmembrane bZIP transcription factor ATF6 (Cox et al, 1993;Shi et al, 1998;Tirasophon et al, 1998;Wang et al, 1998;Harding et al, 1999;Haze et al, 1999;Nakagawa et al, 2000). Ire1 and PERK both have luminal, ER stress-sensing domains that regulate their dimerization and activation of their protein kinase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of ATF6 occurs via a proteolytic cleavage that allows its translocation to the nucleus where it functions as an active transcription factor (Haze et al, 1999). Ire1 and ATF6 are primarily implicated in the transcriptional arm of the UPR, resulting in the induction of ER chaperones to remedy protein misfolding (Tirasophon et al, 1998).In contrast, PERK contributes to the regulation of protein translation and cell adaptation to ER stress (Shi et al, 1998;Harding et al, 1999Harding et al, , 2000bCullinan et al, 2003). Two substrates/effectors of PERK have been identified.…”
mentioning
confidence: 99%